Physical properties and heavy metal (Cu, CD & Pb) determination of organic honey samples from Negros Occidental. - Parcia, Jsra Guillamas
Honey is the natural sweet substance produced by honey bees from the nectar of plants or from secretion of living parts of plants. It contains a complex mixture of carbohydrates and other minor substances. Each of these minor constituents have distinctive nutritional or medicinal properties. However, artificial honey can be produced from carbohydrate sources that have glucose-fructose composition that are within a close range with that of organic honey. Thus, there is a need to characterization honey samples based on their physical properties such as pH, color, and moisture content which serve as important indicators that can help distinguish organic honey from artificial honey. Also present in honey are inorganic compounds such as heavy metals which may be needed by the human body for vital activities. However, if they go beyond the tolerance limits, they could pose as environmental pollutants that are hazardous for human health. Seven (7) sources of organic raw honey were obtained from various locations in Negros Occidental. Sample obtained were collected were from Bacolod City (4), Talisay City (1), Silay City (1), Vitorias City (1) and commercial sample of organic honey from Mindoro was used as a comparative sample. Measured pH values of the honey samples ranged from 3.13-3.37±0.094 which falls within the accepted pH value range of 3.2-6.1. The color of the honey samples ranged from water-white to dark amber. Moisture content ranged from 19.8->25.0 g/100g. Atomic Absorption Spectroscopy analysis of the honey samples for the heavy metals Cu, Cd and Pb measured 0.0014-0.0316ppm, 0.0004-.0091 ppm, and 00.0111-0.0178ppm respectively, which fall below the accepted maximum concentrations of 0.036ppm (Cu), 0.05ppm (Cd) and 0.02ppm (Pb.)